Model Makmal Multiplatfom - Nik Ibrahim, Nik Mat (1999)
Computer hardware is becoming more powerful everyday. For instance, hard disk is growing bigger but the space is not fully utilize except by data intensive applications such as games software. Multiboot enables more than one operating system to share the same hard disk. To optimize the use of Intel x86 computers and to give much choice to the user, it is proposed the setting up of multiplatform lab. Windows 95 and Linux are used in the client computers. Windows 95 is retained because of its popularity while Linux is used to bring the strength of Unix into the lab. It is hoped that the culture of being the passive user in Windows 95 be turned into active user in Linux platform. As fo the present platform such as Windows 95, Windows NT and Netware, they can still be retained and their communication problem can be overcome by using appropriate utilities application.